Broad 4-Hydroxyphenylpyruvate Dioxygenase Inhibitor Herbicide Tolerance in Soybean with an Optimized Enzyme and Expression Cassette . Issue 3 (5th September 2014) - Siehl, Daniel L.; Tao, Yumin; Albert, Henrik; Dong, Yuxia; Heckert, Matthew; Madrigal, Alfredo; Lincoln-Cabatu, Brishette; Lu, Jian; Fenwick, Tamara; Bermudez, Ericka; Sandoval, Marian; Horn, Caroline; et al.
Abstract : A modified native promoter, dual protein localization, and an evolved desensitized maize protein variant enables field tolerance in soybean to multiple herbicides . Abstract: With an optimized expression cassette consisting of the soybean ( Glycine max ) native promoter modified for enhanced expression driving a chimeric gene coding for the soybean native amino-terminal 86 amino acids fused to an insensitive shuffled variant of maize ( Zea mays ) 4-hydroxyphenylpyruvate dioxygenase (HPPD ), we achieved field tolerance in transgenic soybean plants to the HPPD -inhibiting herbicides mesotrione, isoxaflutole, and tembotrione. Directed evolution of maize HPPD was accomplished by progressively incorporating amino acids from naturally occurring diversity and novel substitutions identified by saturation mutagenesis, combined at random through shuffling. Localization of heterologously expressed HPPD mimicked that of the native enzyme, which was shown to be dually targeted to chloroplasts and the cytosol. Analysis of the native soybean HPPD gene revealed two transcription start sites, leading to transcripts encoding two HPPD polypeptides. The N-terminal region of the longer encoded peptide directs proteins to the chloroplast, while the short form remains in the cytosol. In contrast, maize HPPD was found almost exclusively in chloroplasts. Evolved HPPD enzymes showed insensitivity to five inhibitor herbicides. In 2013 field trials, transgenic soybean events made with optimized promoter and HPPD variant expression cassettes were tested with three herbicides and showed tolerance to four times the labeled rates of mesotrione and isoxaflutole and two times the labeled rates of tembotrione.